Gandhi - Attenborough, Richard; Attenborough, Richard; Briley, John, 1940-; Shankar, Ravi, 1920-2012 (Marketed by National Education & Information Films Limited : Distributed by Diskovery Video & Laser Co. Pvt. Ltd., 2006)
Feature film on Mahatma Gandhi, 1869-1948 stressing his philosophy of nonviolence as a technique for political change, from his activities in Southern Africa in the Indian Congress Party (1893) through his return to India (1915), his role in the Indian National Congress Party, and his various campaigns and struggles for Indian independence. Ends with his death by assassination in 1948, just a few months after Indian independence.